Commercial Forms And Applications Of Aluminum And Aluminum Alloys - P. V. Faragher (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
A METAL or alloy finds its place in commerce in proportion to its ability to serve certain purposes better and more economically than other materials. While there is some overlapping of the fields of application of the various metals under discussion in this symposium, each one has its uses for which it is especially adapted. While aluminum is the most recent of the metals to enter the field, the development of the industry has been based on its peculiar properties, by virtue of which new uses for non-ferrous metals have been created. There has been substitution of this new metal for other members of the group but there has been a far greater development in entirely new fields. In common with the other non-ferrous metals, aluminum is resistant to atmospheric corrosion. It also withstands the action of many of the common chemical reagents, strongly alkaline substances being the notable exceptions. The outstanding properties on which the application of aluminum is based are its low specific gravity and its ease of fabrication into the forms in which it is used. It is noteworthy that this property of specific lightness is retained in all the commercial aluminum-base alloys. This statement does not apply to aluminum bronze; this is more properly a copper-base alloy, since aluminum enters into its composition to the extent of only about 10 per cent. None of the commercial casting alloys of aluminum has a density exceeding that of the parent metal by more than about 10 per cent., and some are actually lighter. In the so-called "strong alloys" of aluminum in which strengths comparable to that of mild steel are developed by heat treatment, the greatest increase in density is only slightly more than 3 per cent., and one of these, also, is lighter than aluminum. This property of lightness combined with the desirable mechanical properties of the alloys, makes aluminum especially suited for parts of moving assemblies where saving in power, as well as a decrease in stresses resulting from inertia and vibration, are of importance.